Lesya Ukrainka’s drama "Lisova Pisnya" in literature lessons - Teslenko, Oxana (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2021)
The purpose of the article is to substantiate the choice of methods and ways of analyzing Lesya Ukrainka’s drama-extravaganza "Forest Song" in the context of a competency-based approach to teaching and educating young people by means of the art of words. The statistic looks at the genre-style and the novels of the drama-extravaganza "Lisova Pisnya", the individual style of writing, the artistic officials, the character of creation of characters, the particularity of the problematic of the composition of the work. Typically, I mean those that in the new protist two light – light of reality with living people and light of nature with biological sources, which is the result of the development of science fiction. The main conflict is the struggle against stupidity, youthfulness for a high world, vitality and beauty, for harmony, happiness in life. The compositional structure of the work is enhanced by the role of the prologue-singing as a kind of prelude to future conflicts, the opposition of will and captivity, movement and stagnation; conflict between man and nature: the meeting of the forest child Mavka and the village boy Lukash, the birth and flowering of love, the development of the conflict between poetry and prose, dream and everyday life, the vicissitudes of love, which are the plot of the drama. Its feature is emphasized by two culminating peaks, which in the third act reach the deepest struggle of passions. The article offers methodical recommendations for the analysis of the drama extravaganza "Forest Song" in accordance with the requirements of the competence approach to the literary education of students: take advantage of the mixed path of analysis of a literary work.